PENGARUH ADITIF ADERCO TERHADAP SPECIFIC FUEL CONSUMPTION (SFC) PADA MESIN DIESEL DI PLTD LUWUK BANGGAI SULAWESI TENGAH - Moch. Syaiful Anwar; Mochamad Shaleh (Universitas Majalengka, 2025)
Electricity demand in Luwuk Banggai Sulawesi Tengah has continued to increase, requiring efficient operation of diesel power plants. The use of Biodiesel B35 as an alternative fuel introduces challenges related to lower fuel efficiency compared to conventional diesel. This study aims to evaluate the effect of Aderco additive on improving fuel efficiency in diesel engines at Luwuk Diesel Power Plant. A field experimental method was applied using a pre-test and post-test design by comparing engine performance before and after additive application. The analysis focuses on Specific Fuel Consumption as the main performance indicator, calculated from fuel consumption and power output under similar operating conditions. The results show that the use of Aderco additive reduces Specific Fuel Consumption in all tested units. Medium-speed engines demonstrate a more significant improvement, with a maximum reduction of 4.68%, while high-speed engines show a smaller decrease ranging from 1.02% to 1.35%. These findings indicate that the effectiveness of the additive is influenced by engine speed and combustion duration. In conclusion, the Aderco additive effectively improves fuel efficiency in diesel engines, particularly in medium-speed units, without requiring modifications to engine design.